Hans Kelsen and the Austrian Constitutional Court (1918-1929) (2012)
This article intends to examine Hans Kelsen’s contribution to the establishing of the first Austrian Constitutional court, analyzing the key differences between Kelsen’s model of Constitutional court and that of his German mentor, the Jurist Georg Jelline